The use of graphic novels in the English as a foreign language EFL context: Fun Home: A Family Tragicomic, identity and intertextuality - Muñoz Sánchez, Tania (Journal of Artistic Creation and Literary Research, 2025)
The present research arises from the idea of the pedagogic potential of graphic novels in the classroom and offers fresh insights on how to promote intertextual connections in reading classrooms using this new pedagogical tool in the foreign language environments. With regards to methodology, firstly there is a broad overview on graphic novels, if will first attempt to define the genre and clarify the assumption that comics and graphic novels are the same thing. Secondly, there is a briefly trace of the historical evolution of the genre, and focus on some aesthetic aspects, relevant to the process of reading comprehension. Finally, the research ends with the analysis of a case study, an example that takes the form of sequential art, known as “Fun Home: A Family Tragicomic” by Alison Bechdel where students are able to bring their own experiences to the text, interact with it and learn about Anglo-American literary history as well as the gender dynamics.